Improving Sleep Quality in Stroke and Chronic Kidney Disease Patients: A Systematic Review of Non-Pharmacological Interventions - Yudia Eriza; I Made Kariasa; Liya Arista; Sri Yona (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2026)
Sleep disturbances are common in patients with stroke and chronic kidney disease, potentially worsening health conditions and reducing quality of life. Non-pharmacological interventions have received less research attention, despite the potential for non-pharmacological approaches to improve sleep quality without causing side effects. This systematic review aimed to evaluate the effectiveness of non-pharmacological interventions in this population. Randomized controlled trials involving patients with stroke and chronic kidney disease aged >18 years were searched in seven English-language databases. Methodological quality was assessed using the JBI critical appraisal tool, and data were synthesized. 9 RCTs met inclusion criteria and demonstrated significant benefits. Cognitive Behavioral Therapy (4 studies) consistently improved sleep quality and reduced fatigue, anxiety, and depression (p < 0.001). Reflexology (2 studies) decreased anxiety and improved sleep quality (p < 0.001). Acupuncture significantly improved ISI, PSQI, and HADS scores (p < 0.001–0.003). Lavender aromatherapy reduced depression and improved sleep quality (p < 0.001), while spiritual care improved sleep quality and spiritual well-being (p < 0.001). These findings highlight the role of nurses in implementing non-pharmacological interventions to address sleep disturbances and related psychological symptoms in patients with stroke and chronic kidney disease. Cognitive Behavioral Therapy is recommended for patients with insomnia and psychological comorbidities, reflexology and massage may be beneficial for those undergoing hemodialysis, while acupuncture, aromatherapy, and spiritual care can be tailored to individual needs. Further research is needed to assess their long-term effectiveness and their integration into broader clinical practice.